Investigating the Relation between Targeting Strategy and Green Brand Positioning Strategy: A Qualitative Exploratory Study - Mihai STOICA (Communications of International Proceedings, 2021)
The purpose of this paper is to provide a perspective on the relation between targeting strategy and green brand positioning strategy. The research method used was the in-depth individual interview, conducted among specialists from organic certified companies, who have in their portfolio a green brand which they sell on the organic food market in Romania. In order to provide an integrative view on the analyzed topic, the research was conducted among manufacturers, processors, distributors and retailers. The results showed that in the case of targeting the mass market, the selected positioning bases selected are mainly from the category of those specific to conventional products, while the importance of green positioning bases decreases (positioning at standards imposed by the legislation in force). On the other hand, if the company chooses to address only the segment of green consumers, then it is more likely that the company opts for those attributes and benefits that define green products (positioning above the standards imposed by the legislation in force). This paper offers a view on how to select the positioning bases needed to define the green brand positioning, taking into account the strategy chosen on a higher level (targeting strategy).
Keywords: Green Brand Positioning; Green Marketing Strategies; Market-Targeting Strategies; Organic Food.